Metode Membentuk Akhlak Mulia dalam Pendidikan Islam - Afri Naldi; Rakha Aditya Putra; Wildan Satio; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of writing this paper is to discuss methods of forming noble character in Islamic education. Many see in the current generation that students do not implement noble character in everyday life. Morals are everything related to good or bad human actions. The understanding of morality in Islam is based on the Al-Qur'an and Hadith, which provide guidelines and examples of good behavior that must be followed by Muslims. The aim of morality in Islam is to form good character and improve human behavior so that they become responsible individuals. The research method used is library research. In this paper the author will discuss the meaning, distribution of morals and methods of forming noble morals in Islamic education by using exemplary methods, habituation, advice, stories and punishments so that students re-implement noble morals in their daily lives.